Gastroenterologic endoscopy - Sivak, Michael V; Schleutermann, Donna A (W.B. Saunders, 2000)
Case Western Reserve Univ., Cleveland, OH. Provides a standard reference encompassing every aspect of endoscopy and presents a procedurally oriented discipline in textbook format. Halftone illustrations. For surgeons and clinicians. CD-ROM is not yet available. Previous edition: c1986. Added to Brandon-Hill medical list 4/01. DNLM: Endoscopy, Gastrointestinal--methods.
Keywords: gastrointestinální nemoci; Endoscopy, Digestive System; gastroenterologie; endoskopie trávicího systému; radiologie, nukleární medicína a zobrazovací metody; Gastrointestinal Diseases